2003
DOI: 10.1373/49.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Rapid HPLC-Electrospray Tandem Mass Spectrometric Assay for Urinary Testosterone and Dihydrotestosterone Glucuronides from Patients with Benign Prostate Hyperplasia

Abstract: by the locus-specific primer is directly subjected to TaqI digestion and is analyzed on an agarose gel without radioisotopic hybridization. It also appears to be more accurate because all three distinct chimeric CYP21P/ CYP21 genes had 3.2-kb fragments (Fig. 1C, lanes 3 and 4). Simply assuming that the 3.2-kb fragment from conventional Southern analysis (6 ) is a deletion of the CYP21 gene has been shown to be incorrect. The authors of one report have stated that the 3.2-kb fragment analyzed by Southern blotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…The highest concentration androgen glucuronide was An-3G (2.4 ± 0.5 μg/mL), followed by 11β-OHAn-3G (0.7 ± 0.2 μg/mL), DHEA-3G (41.0 ± 15.7 ng/mL), T-17G (31.7 ± 15.6 ng/mL), Epi-17G (26.2 ± 16.1 ng/mL) and DHT-17G (22.3 ± 6.8 ng/mL). The levels of individual androgen glucuronides measured are in accordance with those of previous reports (Weykamp et al, 1989;Choi et al, 2000Choi et al, , 2003. In our previous report, the levels of urinary androgen glucuronides from subjects well-matched for sex, age and ethnic group with subjects from this study were detected using high-temperature GC-MS (Choi et al, 2000).…”
Section: Application To the Urine Samplessupporting
confidence: 92%
See 1 more Smart Citation
“…The highest concentration androgen glucuronide was An-3G (2.4 ± 0.5 μg/mL), followed by 11β-OHAn-3G (0.7 ± 0.2 μg/mL), DHEA-3G (41.0 ± 15.7 ng/mL), T-17G (31.7 ± 15.6 ng/mL), Epi-17G (26.2 ± 16.1 ng/mL) and DHT-17G (22.3 ± 6.8 ng/mL). The levels of individual androgen glucuronides measured are in accordance with those of previous reports (Weykamp et al, 1989;Choi et al, 2000Choi et al, , 2003. In our previous report, the levels of urinary androgen glucuronides from subjects well-matched for sex, age and ethnic group with subjects from this study were detected using high-temperature GC-MS (Choi et al, 2000).…”
Section: Application To the Urine Samplessupporting
confidence: 92%
“…Hence, glucuronidation plays an important role in regulating the levels of androgens, and the measurement of urinary androgen glucuronides is very important in androgen metabolism. Because of changed androgen metabolism, urinary androgen glucuronide levels are altered in various diseases, such as BPH (Choi et al, 2003), acne (Garmina et al, 2002) and alopecia (Legro et al, 1994). As a result, androgen glucuronides can be used as biomedical indicators in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A dendrogram of ratios revealed that the oxidoreductases formed a cluster (5␣-reductase, 3␣-HSD, 3␤-HSD, and 17␤-HSD, except for 20␣-HSD; see Supplementary Table 1 for full enzyme names), which are differentiated with a cytochrome P450 enzyme, 11␤-hydroxylase. These results support the validity of the data transformation, since 5␣-reductase is a marker of BPH [27][28][29], and 17␤-HSD is positively expressed in prostate cells [40,41]. Other up-regulated enzymes in the map might be biomarkers of BPH.…”
Section: Steroid Signatures By Hierarchical Clustering Analysissupporting
confidence: 79%
“…The aim of this study was to validate a GC-MS profiling method and a method that allows the quantitative visualization of multiple urinary steroids. To visualize quantitative results, a microarray map (a type of heat map) was designed to present the urine sample results of 59 patients with benign prostatic hyperplasia (BPH) and 41 healthy male subjects; BPH was chosen because steroid metabolism is known to play a role in the progress of prostate diseases [27][28][29]. This study focused on illustrating the usefulness of steroid signatures for explaining both the concentrations of individual steroids and the activities of enzymes correlated global steroidogenesis in BPH, and suggest that enzyme activity profiling may be a useful diagnostic tool and provide a means of identifying mining biomarkers in hormone-dependent diseases.…”
mentioning
confidence: 99%
“…There are many naturally occurring steroids that are excreted mainly through the urine by their water-soluble conjugates formed by the substitution of 3-or 17-hydroxyl groups with either sulfate or β-glucuronide (1), and their direct measurements have been introduced to clinical studies (2)(3)(4)(5). Gas chromatography-mass spectrometry (GC-MS)-based profiling is a proven technique in steroid analysis, whereas immunoassays have limited applicability due to cross-reactions (6,7).…”
Section: Introductionmentioning
confidence: 99%